Relationship between Human Development Index and Gross Regional Domestic Product on Sanitation Access in East Java Region in Achieving Sustainable Development Goals - Moh Rizal Ngambah Sagara; Mega Mutiara Sari; Iva Yenis Septiariva; I Wayan Koko Suryawan (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
The policy of full access to sanitation through the Sustainable Development Goals (SDGs) (2015–2030) requires community participation. The role of society in this regard can depend on the Human Development Index (HDI) and Gross Regional Domestic Product (GRDP). The incidence of diarrhea in all age groups is only 3.5%. East Java is a province that contributes significantly to the number of cases of diarrhea in children under five in Indonesia, so sanitation is critical. This study aimed to determine the effect of HDI and GRDP simultaneously on sanitation access in districts and cities in East Java Province. This research was conducted using secondary data from the Central Statistics Agency of East Java Province. The data analysis method used is multiple linear. HDI and GRDP variables positively and significantly impact the number of sanitation access districts and cities of East Java Province in 2016-2019. GRDP partially has a regression coefficient of 0.223 greater than HDI, which means that an increase in GRDP by one unit of rupiah causes an increase in the achievement of sanitation access in East Java Province. As policymakers and implementers, local governments must pay attention to HDI and GRDP to access proper sanitation in East Java Province.